'Florida Blizzard' Caladium - A University of Florida Cultivar - Brent K. Harbaugh; B. D. Miranda; G. J. Wilfert (EDIS, 2004)
Caladiums [Caladium bicolor (Ait.) Vent., syn. Caladiumxhortulanum Birdsey, Araceae Juss.] are tropical foliage plants possessing diversity of leaf colors and shapes found in few cultivated plants. 'Florida Blizzard' is derived from a cross between the popular white heart-shaped leaf caladium cultivars 'Aaron' and 'White Christmas', initially was evaluated in 1993 as GC93-715. This document is ENH963, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 25, 2003.